2014
DOI: 10.1063/1.4899072
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-particle energy spectra in local reduced density matrix functional theory

Abstract: Orbital-dependent correlation energy in density-functional theory based on a second-order perturbation approach: Success and failure J. Chem. Phys. 123, 062204 (2005) (2014)] local reduced density matrix functional theory (local RDMFT), a theoretical scheme capable of incorporating static correlation effects in Kohn-Sham equations. Here, we apply local RDMFT to molecular systems of relatively large size, as a demonstration of its computational efficiency and its accuracy in predicting single-electron propertie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…The relative differences for all functionals lie in the range of 32%-463%. This is largely expected since local-RDMFT energy eigenvalues have been proven to give accurate approximations to the experimental IPs 24,25 contrary to the LDA ones. The big difference from the LDA eigenvalues can be partly attributed to constraints (3) and (4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative differences for all functionals lie in the range of 32%-463%. This is largely expected since local-RDMFT energy eigenvalues have been proven to give accurate approximations to the experimental IPs 24,25 contrary to the LDA ones. The big difference from the LDA eigenvalues can be partly attributed to constraints (3) and (4).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from reducing the numerical cost, the local-RDMFT framework provides an energy eigenvalue spectrum connected to the LROs. We found that the energy eigenvalues of the strongly occupied orbitals reproduce the ionization potentials of small and large molecules 24,25 accurately. We now turn our attention to the question of how the LROs compare with different sets of orbitals like the almost exact NOs taken from MCSCF calculations, those from the full RDMFT minimization, and the KS orbitals of LDA.…”
Section: Local Rdmftmentioning
confidence: 92%
See 1 more Smart Citation
“…In practice, however, the correlation energy is an unknown functional of the 1-RDM and must be approximated. Although there are several known approximations for the xc energy functional [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], the most promising for extended systems is the power functional [14,15] where the xc energy reads…”
Section: Introductionmentioning
confidence: 99%
“…Properties like spectra or static response functions, like static dipole polarizabilities [102], however are not directly accessible. Several methods have been proposed to estimate photoemission spectra starting from Slater's transition state [70,103], local RDMFT [104,105] and approximations in terms of higher order RDMs [69]. Applications of these approaches to models systems [18,69] as well as real materials [69][70][71] showed mixed performances.…”
Section: Gaps and Spectral Informationmentioning
confidence: 99%